The three-dimensional shoulder pain alignment (3D-SPA) mobilization improves pain-free shoulder range, functional reach and sleep following stroke: a pilot randomized control trial. Issue 21 (8th October 2020) - Pain, Liza A. M.; Baker, Ross; Sohail, Qazi Zain; Hebert, Debbie; Zabjek, Karl; Richardson, Denyse; Agur, Anne M. R.
Abstract: Background and purpose: Following a stroke, three-dimensional clavicular/scapular/humeral joint rotations may become restricted and contribute to post-stroke shoulder pain. This study examined whether a treatment group provided with current standard treatment plus the proposed "Three-dimensional Shoulder Pain Alignment" mobilization protocol demonstrated improved pain-free shoulder range, functional reach and sleep compared to a control group provided with standard treatment alone. Methods: In this double-blinded parallel-group randomized control trial, treatment and control subjects with moderate/severe post-stroke upper extremity impairment and shoulder pain were treated 3x/week for 4 weeks. Outcome measures included changes in pain-free three-dimensional clavicular/scapular/humeral range (using computerized digitization), pain during sleep and functional reach (using the Pain Intensity-Numerical Rating Scale), and pain location/prognostic indicators (using the Chedoke-McMaster Stroke Assessment-Shoulder Pain Inventory). Results: Compared to controls ( n  = 10) the treatment group ( n  = 10) demonstrated significantly improved three-dimensional clavicular/scapular/humeral pain-free range during shoulder flexion and abduction ( p  < 0.05; Hedges g  > 0.80), large effect sizes for decreased pain during sleep and functional reach to the head and back (OR range: 5.44-21.00), and moderate effect size for improved pain/prognostic indicators (OR = 3.86). Conclusions: The Three-Dimensional Shoulder Pain Alignment mobilization protocol significantly improved pain-free range of motion, functional reach and pain during sleep in shoulders with moderate/severe post-stroke upper-extremity impairment. Implications for rehabilitation: Although three-dimensional clavicular/scapular/humeral rotations are an essential component of normal pain-free shoulder range of motion, current guidelines for treatment of post-stroke shoulder pain only includes uni-dimensional mobilizations for joint alignment and pain management. The Three-Dimensional Shoulder Pain Alignment (3D-SPA) mobilization protocol incorporates multi-dimensional mobilizations in various planes of shoulder movement. The current study results demonstrate proof-of-concept regarding the 3D-SPA mobilization, and this approach should be considered as an alternative to the uni-dimensional mobilizations currently used in clinical treatment guidelines for post-stroke shoulder pain.